The use of exercises in closed kinetic chain and open kinetic chain after ligamentoplasty of anterior cruciate ligament: A literature review (Research, Society and Development, 2023)
The Anterior Cruciate Ligament is one of the main biomechanical stabilizers against external rotational forces, being the most common type of knee injury. The objective of this study was to carry out a literature review and find scientific evidence on exercises in OKC and CCF in the process of early rehabilitation after ACL reconstruction. The study is a systematic literature review carried out in the following databases: Scielo, PubMed and Pedro, including 20 articles for analyzing the results. Inclusion criteria included subjects in post-surgical recovery from an anterior cruciate ligament injury, regardless of ethnicity, sex, age and nationality. The results demonstrate that exercise in an OKC without weight addition and a restricted ROM after ACL reconstruction at an early stage of rehabilitation showed a significantly better outcome in the reduction of anterior laxity and improvement of pain, in addition to achieving a faster recovery for the strength of the knee extensor muscles.